Dose-guided individualized planning target volume margin optimization in nasopharyngeal carcinoma: a retrospective megavoltage computed tomography–based cumulative analysis - Yuan, Xingxing; Xu, Longfei; Gong, Changfei; Jian, Junming; Zheng, Wenheng; Luo, Changwei; Zhang, Yun (Frontiers in Oncology, 2026)
BackgroundIn radiotherapy for nasopharyngeal carcinoma (NPC), balancing target coverage with protection of adjacent organs remains challenging. This study aimed to evaluated the cumulative dose deviations resulting from different planning target volume (PTV) margins during tomotherapy (TOMO) using megavoltage computed tomography (MVCT) and investigated the feasibility of individualized margin optimization, with the goal of minimizing volume and protecting surrounding tissues.MethodsForty patients with NPC treated with TOMO were retrospectively analyzed. Daily MVCT scans were acquired throughout treatment. Using deformable image registration, the dose from each fraction was mapped to the planning CT, and cumulative doses were reconstructed using MIM software. For each patient, isotropic 1–4 mm virtual expansions were applied to the gross tumor volume (GTV) and clinical target volume (CTV) to generate “virtual” structures. These were evaluated for V100% dose coverage under the accumulated dose. Planned and accumulated doses were compared across expansion margins using V100%, D95%, conformity index, and homogeneity index, with differences assessed by paired t-tests. Dose variations in organs at risk (OARs) were also assessed.ResultsPlanned and accumulated V100% doses were within 5% for most targets, however, certain virtual expansions demonstrated detectable dose discrepancies. For GTVnx, a +2 mm margin significantly reduced accumulated V100% (96.55% ± 3.04%) compared with the planned dose (99.18% ± 0.73%; p < 0.001). For GTVnd, both +1 mm and +2 mm margins significantly reduced accumulated V100% (99.21% ± 1.17% and 99.20% ± 1.17%, respectively; p < 0.01). For CTV1, a +2 mm margin yielded higher accumulated V100% (99.57% ± 1.49%) than planned (99.89% ± 0.21%; p = 0.212), suggesting deformation-related over-coverage. Larger margins (3–4 mm) reduced coverage, though not significantly. For CTV2, accumulated V100% remained consistent across all margins. The +1 mm expansion produced a small but significant increase (99.72% ± 0.38% vs 99.99% ± 0.23%; p = 0.006), while larger expansions (2–4 mm) had no effect, suggesting 1–2 mm may be optimal.ConclusionMVCT-based cumulative dose evaluation provides a more accurate assessment of the delivered dose than conventional geometric methods. Individualized, dose-driven PTV margin strategies may improve tumor coverage while minimizing OAR exposure, thereby advancing precision radiotherapy for NPC.